2021
DOI: 10.1002/gps.5613
|View full text |Cite
|
Sign up to set email alerts
|

The role of education and income for cognitive functioning in old age: A cross‐country comparison

Abstract: Objectives Previous studies have shown that higher education promotes cognitive health. This effect, however, is embedded in the living conditions of a particular country. Since it is not clear to what extent the country and its specific living standards are necessary preconditions for the observed effect, we investigated whether the impact of education and income on cognitive functioning differs between countries. Methods Analyses were based on harmonized data from the World Health Organization's multi‐countr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…One study at country level, found that the aggregated effect of education was twice the effect of income on cognitive functioning in adult aged 50 years and older, and thus indirectly moderated the effect of income on cognitive functioning. They further report that the effect sizes varied strongly between countries, concluding that country’s GDP per-capita seems to influence cognitive functioning [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…One study at country level, found that the aggregated effect of education was twice the effect of income on cognitive functioning in adult aged 50 years and older, and thus indirectly moderated the effect of income on cognitive functioning. They further report that the effect sizes varied strongly between countries, concluding that country’s GDP per-capita seems to influence cognitive functioning [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, education and income were reported to impact cognitive performance in people aged ≥50 years [ 35 ]. A systematic review indicated that individuals had cognitive impairment during the first episode of depression and those with multiple episodes showed more severe cognitive impairment [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…First, more educated older adults have higher health literacy, so there is a positive correlation between OAE and health literacy; such education is associated with better health and survival ( 37 ). Second, higher levels of education help individuals to build psychosocial resources; increased education can prevent cognitive impairment in older adults ( 47 ). Third, people with higher levels of education are more likely to adopt positive health behaviors, compared with people who have lower levels of education; in this context, positive health behaviors include regular exercise, moderate alcohol consumption, and avoidance of smoking.…”
Section: Challenges Of Oaementioning
confidence: 99%